Platelet Count, ADAMTS13 Activity, von Willebrand Factor Level and Survival in Patients with Colorectal Cancer: 5-Year Follow-up Study - Garam, Nóra; Maláti, Éva; Sinkovits, György; Gombos, Tímea; Szederjesi, Attila; Barabás, Loránd; Gráf, László; Kocsis, Judit; Prohászka, Zoltán (Thrombosis and Haemostasis, 2018)
Distant metastasis is a major cause of colorectal cancer–related death, but the mechanism of tumour progression is not fully understood. There is growing evidence of an interaction between tumour cells and platelets which may influence tumour progression and metastasis formation. Quality and quantity of von Willebrand factor may regulate the interaction between tumour cells and platelets. Our aim was to measure the platelet count, von Willebrand factor antigen (VWF:Ag) levels and ADAMTS13 activity in a large (n = 232) cohort of colorectal cancer patients and to examine their relationships with the stage of the disease and 5-year survival without thrombotic complications using multivariable models. Significantly higher platelet counts (p = 0.005), VWF:Ag levels (p = 0.008) and decreased ADAMTS13 activity (p = 0.006) were observed in patients with metastatic disease. Results of the Kaplan–Meier analysis showed that lower platelet counts (p < 0.0001), lower VWF:Ag (p = 0.0008) levels and higher ADAMTS13 activity (p < 0.0001) were associated with better event-free survival. Finally, to investigate the association between overall event-free survival and the three study variables, multivariate Cox proportional hazard models were generated. All models were adjusted for age, gender and disease stage. Platelet count, ADAMTS13 activity or VWF:Ag level were incorporated and all of these variables turned out to be age-, gender- and stage-independent predictors of mortality (all hazard ratio >1.7, p < 0.05). In summary, this is the first observational study reporting association between higher mortality or thrombotic complications and increased platelet count, increased VWF:Ag levels and decreased ADAMTS13 activity in colorectal cancer.
Keywords: ADAMTS13; platelet; von Willebrand factor; mortality; colorectal cancer